Development of ready-to-drink (RTD) potato milk enriched with spirulina powder using response surface methodology (RSM) - Urag, Amanda Gaye A.; Pagulayan, Jin Mark DG. (Quezon City University of the Philippines Diliman, 2024)
The study aimed to develop a ready-to-drink potato milk enriched with spirulina. Specifically, it evaluated the effect of different amounts of spirulina and carrageenan powders on the physicochemical properties and consumer acceptability of the product using response surface methodology. The amount of spirulina and carrageenan were found to have a significant (p<0.05) effect on the protein content, total soluble solids, and aroma and flavor acceptability of the product. The optimized parameters for the product involved minimized amounts of spirulina and carrageenan which were 0.25 g/100ml and 0.011 g/100ml, respectively which resulted in a potato milk sample with maximum protein content and consumer acceptability score. Verification studies found that the developed statistical models were accurate in predicting the responses for the study. The optimized product had a pH of 6.18, total soluble solids content (TSS) of 10.0°Bx, characterized of having a dark greenish-brown color based on the generated hue (H°) and chroma (C*) values of 102.63 and 14.27, respectively. In addition, the optimized product had a moisture content, ash content, protein content, and carbohydrate content of 87.18 ± 0.02%, 0.10 ± 0.01%, 0.45 ± 0.11%, and 12.20 ± 0.04%, respectively. The study provides more information on the use of potatoes and spirulina as ingredients in plant-based milk products. Moreover, preliminary data from this study may be used to explore the possibility of utilizing other niche ingredients in improving the nutritive quality of plant-based milk products.
In partial fulfillment for the Degree of Bachelor of Science in Food Technology
Thesis
Keywords: Cooking (Spirulina); Functional foods; Plant-based milk; Potato milk; Response surface methodology